Lithium ion battery
By using nitrile compounds as the positive electrode protection additive and the first additive with a specific structure as the negative electrode protection additive in lithium-ion batteries, the problem of short battery cycle life under high temperature cycle conditions is solved, and the effect of significantly improving the high temperature cycle performance and cycle life of the battery is achieved.
Patent Information
- Application Number
- CN202510288805.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The existing lithium-ion batteries have a short cycle life under high temperature cycling conditions, which is mainly due to the deterioration of nitrile additives on the negative electrode, resulting in poor quality of SEI film and accelerated electrolyte consumption, which affects battery performance.
The second additive containing a nitrile compound is used as the positive electrode protection additive, and the dissolution of the positive electrode is suppressed by complexing the high-valent transition metal ions; at the same time, a uniform and stable SEI film is formed on the surface of the negative electrode by using the first additive with a specific structure as the negative electrode protection additive, thereby inhibiting the deterioration of the nitrile to the negative electrode.
It significantly improves the high-temperature cycling performance and cycle life of lithium-ion batteries, delays electrolyte consumption, and ensures efficient output of the battery during the entire life cycle.
Smart Images

Figure BDA0005307943670000021 
Figure BDA0005307943670000081 
Figure BDA0005307943670000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium ion battery capable of improving high temperature cycle performance. Background Art
[0002] Lithium-ion batteries have been widely used in the field of portable electronic products due to their high operating voltage, high safety, long life, and no memory effect. With the increase in the frequency of daily use of electronic products, the requirements for battery cycle life are also getting higher and higher; and the demand for electronic products to be light and portable requires batteries to have high energy density, which is usually achieved by matching high voltage; however, high voltage often leads to a significant reduction in the cycle life of the battery. This is because in the late stage of the cycle, the SEI film is damaged and the electrolyte dries up, causing large-scale side reactions and rapid battery performance degradation.
[0003] In order to adapt to high voltage and improve the cycle life of electronic product batteries, some studies add nitriles to the electrolyte of lithium-ion batteries as positive electrode protection additives. Although the high-voltage stability of lithium-ion batteries has been improved to a certain extent, and high-temperature storage has been significantly improved, nitrile additives are incompatible with the negative electrode and are easy to damage the negative electrode interface, resulting in a decrease in high-temperature cycle performance. Therefore, finding ways to improve high-voltage stability while taking into account high-temperature storage performance and high-temperature cycle performance is a hot research direction in the field of power lithium-ion batteries. Summary of the invention
[0004] In order to solve the technical problem that the high temperature cycle performance of batteries using non-aqueous electrolytes containing nitrile additives is reduced, the present invention provides a lithium ion battery that takes both high temperature storage performance and high temperature cycle performance into consideration.
[0005] The present invention adopts the following technical solutions:
[0006] A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a non-aqueous electrolyte;
[0007] The negative electrode sheet comprises a negative electrode material layer containing a negative electrode active material, wherein the negative electrode active material comprises graphite, and the order degree of the negative electrode active material is R=I D / I G In the spectrum measured by Raman spectroscopy of the negative electrode using a laser with a wavelength of 532nm to 785nm, I D Appears at 1300cm -1 Up to 1400cm -1 The peak intensity of the inner D peak, I G Appears at 1530cm -1 Up to 1630cm -1 The peak intensity of the inner D peak;
[0008] The non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive;
[0009] The additives include a first additive and a second additive, wherein the first additive includes at least one of the following compounds:
[0010]
[0011] The second additive includes at least one of succinonitrile, adiponitrile or 1,3,6-hexanetrinitrile;
[0012] The lithium-ion battery meets the following conditions:
[0013] 2≤[(A+B) / R]×Y≤48, 0.1≤A≤3, 0.5≤B≤5, 0.1≤R≤1, 0.8≤Y≤1.8;
[0014] Wherein, A is the mass percentage of the first additive in the non-aqueous electrolyte, in %;
[0015] B is the mass percentage of the second additive in the non-aqueous electrolyte, in %;
[0016] R is the degree of order of the negative electrode active material;
[0017] Y is the ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery, in g / Ah.
[0018] The lithium ion battery of the present invention adopts a second additive comprising a nitrile compound as a positive electrode protective additive, which can complex the high-valent transition metal ions of the positive electrode and inhibit the dissolution of the transition metal ions, thereby improving the stability of the positive electrode under high voltage and the high-temperature storage performance of the battery. However, nitriles have a deteriorating effect on the negative electrode. From the purpose of protecting the negative electrode, a first additive with a specific structure is used in a non-electrolyte as an efficient negative electrode protective additive, which can form a uniform and stable SEI film on the surface of the negative electrode, while retaining the improvement effect of nitriles on high-temperature storage, while inhibiting the degradation of nitriles to the negative electrode.
[0019] However, the degradation of the negative electrode by the second additive is not only reflected in the effect of the second additive on the film formation of the negative electrode. The cyanide group of the second additive has strong electronegativity, which prompts it to form a solvation structure with the solvent EC and lithium ions, affecting the film formation of the negative electrode, resulting in poor film formation quality of the negative electrode SEI film. The solvent is further reduced at the negative electrode, which reduces the order of the negative electrode active material and rapidly reduces the cycle performance of the battery. By limiting the order of the negative electrode active material, the negative impact of the solvation structure formed by the second additive on the reduction of the order of the negative electrode active material is offset, thereby achieving the purpose of extending the battery cycle life.
[0020] The quality of the electrolyte affects the cycle performance of the battery. The electrolyte is consumed during the battery cycle, especially when the battery is matched with high voltage, which will accelerate the consumption of the electrolyte. In the later stage of the battery cycle, the electrolyte may be too little or even dry. Therefore, the amount of electrolyte that matches the battery discharge capacity is required. Moreover, the lower the ratio of the quality of the battery electrolyte to the battery discharge capacity, the more likely it is that the single-point electrolyte will dry up on the negative electrode surface, thereby amplifying the degradation of the negative electrode by the second additive.
[0021] After extensive research, the inventors found that when the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive in the non-aqueous electrolyte, the degree of order R of the negative electrode active material, and the ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery satisfy 2≤[(A+B) / R]×Y≤48, 0.1≤A≤3, 0.5≤B≤5, 0.1≤R≤1, 0.8≤Y≤1.8, the non-aqueous electrolyte, positive electrode, and negative electrode of the lithium-ion battery achieve good coordination, which can not only ensure the stability of the positive electrode and the negative electrode, but also significantly improve the high-temperature cycle performance of the battery. The second additive, as a positive electrode protective additive, can complex the positive electrode high-valent transition metal ions, inhibit the dissolution of the positive electrode metal ions, and thus improve the high-temperature storage performance of the battery. As a negative electrode protection additive, the first additive can form a uniform, stable and high-quality SEI film on the negative electrode surface. While retaining the improvement effect of the second additive on high-temperature storage, it slows down the process of the second additive forming a solvation structure with the solvent EC and lithium ions under the action of its strong electronegative cyanide, reduces its influence on the negative electrode film formation, and thus inhibits the deterioration effect of the second additive on the negative electrode. At the same time, the coordinated use of the first additive and the second additive helps to regulate the order R value of the negative electrode active material, improve the amount of electrolyte retained in the unit battery capacity, reduce the defect sites of the negative electrode, and control the increase in impedance, make up for the degradation loss of the order of the negative electrode active material caused by the solvation structure formed by nitrile-EC-lithium ions, improve the battery cycle performance, and thus extend the cycle life of the lithium-ion battery; ensure that there is still an appropriate amount of electrolyte in the later stage of the battery cycle, and no single-point electrolyte depletion will occur on the negative electrode surface, and the battery performance decay slows down, which significantly improves the cycle performance of the lithium-ion battery and extends the cycle life of the lithium-ion battery, ensuring that the battery can maintain high-efficiency output throughout its life cycle.
[0022] When the relationship between the mass percentage A of the first additive in the lithium-ion battery, the mass percentage B of the second additive in the non-aqueous electrolyte, the order of the negative electrode active material of the negative electrode and the ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery [(A+B) / R]×Y<2, the content of the positive electrode protection additive and the negative electrode protection additive in the non-aqueous electrolyte is too small, and the dissolution of the positive electrode transition metal ions and the formation of a stable SEI film on the surface of the negative electrode cannot be effectively suppressed, and the effect of effectively protecting the positive and negative electrodes cannot be achieved; or when the battery capacity is constant, the order of the negative electrode active material is too large, which affects the freedom of lithium ion deintercalation.
[0023] When the relationship between the mass percentage A of the first additive in the lithium-ion battery, the mass percentage B of the second additive in the non-aqueous electrolyte, the order of the negative electrode active material and the ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery [(A+B) / R]×Y>2, the content of the positive electrode protection additive and the negative electrode protection additive in the non-aqueous electrolyte is too high, resulting in an increase in the impedance of the electrolyte membrane on the negative electrode surface, hindering the deintercalation of lithium ions on the negative electrode surface, and too many solvated structures are formed, which increases the damage to the order of the negative electrode active material. The negative electrode order is too low, and the SEI film formed on the negative electrode surface is uneven, affecting the cycle performance of the lithium-ion battery.
[0024] Preferably, the relationship between the mass percentage A of the first additive, the mass percentage B of the second additive in the non-aqueous electrolyte, the degree of order R of the negative electrode active material and the ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery satisfies 2.8≤[(A+B) / R]×Y≤28. Within this range, the amount of electrolyte in the battery is at a reasonable level, which can ensure sufficient film formation of the first additive A. The film formation of A can better inhibit the damage of the nitrile additive B to the negative electrode, so the R value will be well controlled, further improving the efficiency and speed of lithium ion deintercalation.
[0025] The first additive is used as a negative electrode protection additive. When its content is too high, it will cause the impedance of the electrolyte membrane on the negative electrode surface to be too large, hindering the deintercalation of lithium ions at the negative electrode interface. When its content is too little, with the reorganization of the negative electrode interface film and the consumption of the negative electrode film additive during the battery cycle, the negative electrode becomes unstable, thereby affecting the electrical performance stability of the lithium ion battery. Specifically, the mass percentage A% of the first additive is 0.1%, 0.2%, 0.5%, 0.6%, 0.8%, 1%, 1.1%, 1.2%, 1.3%, 1.5%, 1.6%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.6%, 2.8%, 3% or a range consisting of any two of these values. Preferably, the mass percentage A% of the first additive in the non-aqueous electrolyte is 0.5% to 2%.
[0026] The second additive is used as a positive electrode protection additive. The second additive contains a cyano group or a cyano group. These groups can form a stable interface film on the surface of the positive electrode material, can continuously protect the positive electrode, and prevent the electrolyte components from being oxidized on the positive electrode surface, so as to achieve the purpose of improving the cycle performance of the lithium-ion battery. When its content is too high, the antagonism to the negative electrode additive increases, which will cause the negative electrode to be unstable and affect the stability of the lithium-ion battery; when its content is too low, the purpose of protecting the positive electrode cannot be achieved. Specifically, the mass percentage content B% of the second additive is 0.5%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.7%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range composed of any two of these values. Preferably, the mass percentage content B% of the second additive in the non-aqueous electrolyte is 2-4%.
[0027] Preferably, the second additive includes succinonitrile and 1,3,6-hexanetrinitrile; or the second additive includes adiponitrile and 1,3,6-hexanetrinitrile. When the positive electrode protection additive is a combination of dinitrile and trinitrile, it can ensure that more active sites of the positive electrode material are covered, inhibit the dissolution of positive electrode metal ions, and thus improve the high temperature storage performance of the battery.
[0028] The order of the negative electrode active material affects the electrochemical performance of the negative electrode. The order within a suitable range forms an ordered microporous structure on the surface of the negative electrode, providing a uniform and efficient transmission channel for lithium ions, facilitating the deintercalation of lithium ions on the surface of the negative electrode, and facilitating the transmission of lithium ions between the positive and negative electrodes, thereby improving the charging and discharging efficiency and rate of lithium ion batteries; the order within a suitable range can promote the formation of a stable and uniform lithium carbonate protective film on the surface of the negative electrode. During the charging and discharging process, the movement of lithium ions is more stable, which is conducive to increasing the number of cycles and service life of lithium ion batteries. The present invention controls the order of the negative electrode active material to be within the range of 0.1 to 1, which is more conducive to forming a stable SEI film on the surface of the negative electrode, increasing the lithium ion conduction rate, and thus improving the cycle performance of the lithium ion battery. In some embodiments of the invention, the order R of the negative electrode active material is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or a range consisting of any two of these values. Preferably, the order R of the negative electrode active material is 0.3 to 0.8.
[0029] Specifically, in some embodiments of the present invention, the order of the negative electrode active material is determined by the following method:
[0030] The lithium-ion battery was discharged to 2.75V at a current of 0.1C, and the lithium-ion battery was disassembled in a glove box filled with argon to obtain the negative electrode sheet. The obtained negative electrode sheet was cut into test samples of 100μm×100μm size, and soaked and cleaned with a low-boiling dimethyl carbonate (DMC) solvent. After being completely dried, it was pasted on the sample stage with the surface of the negative electrode material layer facing away from the current collector facing upward, and then tested.
[0031] The specific test conditions and steps are as follows: Use a laser microscopic confocal Raman spectrometer to scan the graphite particles in the area. The laser wavelength of the Raman spectrometer can be in the range of 532nm to 785nm. Scan to obtain 5μm 2 The D peak and G peak of graphite particles in the range of 1300 cm -1 Up to 1400cm -1 The G peak appears at 1530cm -1 Up to 1630cm -1 The data were processed by LabSpec software to obtain the peak intensities of the D peak and G peak of each graphite particle, which are I D and I G , and then calculate the I of each graphite particle D / I G Ratio, taking the I of all graphite negative electrode particles measured within this range D / I G The average value of the ratios is taken as the order degree R value of the negative electrode active material.
[0032] I D / I G The value reflects the lattice defect and crystallinity of graphite, I D The value is the peak intensity of the D peak, which reflects the degree of defect of the negative electrode active material. The D peak is the shift range of 1300cm in the spectrum tested by Raman spectroscopy analysis of the negative electrode. -1 Up to 1400cm -1 The peak is caused by material defects, I G The value is the peak intensity of the G peak, which reflects the degree of crystallization of graphite. The G peak is the shift range of 1530cm in the spectrum tested by Raman spectroscopy analysis of the negative electrode. -1 Up to 1630cm -1 The peak is caused by the stretching vibration between sp2 carbon atoms, which corresponds to the vibration of E2g optical phonon in the center of the Brillouin zone (carbon atom in-plane vibration). D / I G The larger the value, the more defects and higher disorder of graphite. D / I G The value depends on the carbon source used to prepare graphite, the preparation method used, and the process conditions.
[0033] The ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery reflects the amount of electrolyte retained in the unit battery capacity. Since the electrolyte is continuously consumed as the number of cycles increases, the battery cycle dive is delayed and the battery cycle performance is improved by controlling the ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery. Specifically, in some embodiments of the present invention, the ratio Y of the mass of the electrolyte to the discharge capacity of the battery is 0.8g / Ah, 0.9g / Ah, 1g / Ah, 1.1g / Ah, 1.2g / Ah, 1.3g / Ah, 1.4g / Ah, 1.5g / Ah, 1.6g / Ah, 1.7g / Ah, 1.8g / Ah or a range consisting of any two of these values; preferably, the ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery is 0.9 to 1.4g / Ah.
[0034] Specifically, in some embodiments of the present invention, the mass of the non-aqueous electrolyte in the lithium-ion battery = the mass of the battery after capacity separation - the mass of the battery before liquid injection, or the mass of the non-aqueous electrolyte in the lithium-ion battery = the total amount of liquid squeezed out of the battery cell after capacity separation using a centrifuge at a speed of 8000r / min for 20 minutes; the discharge capacity of the battery is the discharge capacity of 3.0V after the battery is fully charged at a current of 0.2C at 25°C and then discharged at a constant current of 0.2C.
[0035] In some preferred embodiments, the second additive includes 1,3,6-hexanetrinitrile and succinonitrile; or the second additive includes 1,3,6-hexanetrinitrile and adiponitrile. In the form of dinitrile + trinitrile, ion complex protection is formed at different sites of the positive electrode, the positive electrode is better protected, the high temperature storage performance of the battery is improved, and the cycle performance is not degraded.
[0036] In some more preferred embodiments, the second additive includes 1,3,6-hexanetrinitrile, succinonitrile and adiponitrile. The three nitrile compounds mentioned above can be combined with dinitriles and trinitriles of different molecular chain lengths and steric hindrance to form better protection for the positive electrode, further improve the high temperature storage performance of the battery without deteriorating the high temperature cycle performance.
[0037] Specifically, in some embodiments of the present invention, the organic solvent includes one or more of cyclic carbonates, chain carbonates, carboxylates and ethers.
[0038] In some preferred embodiments, the cyclic carbonate compound includes one or more of vinylene carbonate, propylene carbonate, ethylene carbonate and butylene carbonate.
[0039] In some preferred embodiments, the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl trifluoroethyl carbonate and bis(2,2,2-trifluoroethyl) carbonate.
[0040] In some preferred embodiments, the carboxylic acid ester includes one or more of propyl propionate, ethyl propionate, methyl propionate, ethyl acetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate, and ethyl trifluoroacetate.
[0041] In some preferred embodiments, the ethers include one or more of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0042] Specifically, in some embodiments of the present invention, the additive further includes an auxiliary additive, and the auxiliary additive includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, and borate compounds.
[0043] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.
[0044] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.
[0045] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1:
[0046]
[0047] In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;
[0048] In some preferred embodiments, the compound represented by structural formula 1 includes at least one of the compounds represented by compounds 1-1 to 1-6 below:
[0049]
[0050] The phosphate compound includes at least one of the compounds shown in the following structural formula 2:
[0051]
[0052] In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number of 1 to 3; more preferably, the compound shown in the structural formula 2 includes at least one of tris(trimethylsilane) phosphate, tris(triethylsilane) phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate and diallyl hexafluoroisopropyl phosphate.
[0053] In some preferred embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
[0054] In some embodiments of the present invention, based on the mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01% to 10%. Specifically, the content of any one of the optional substances in the auxiliary additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%,
[0055] 4.5%, 5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or a range consisting of any two of these values.
[0056] Specifically, in some embodiments of the present invention, the lithium salt also includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LiPO2F2, LiBF4, LiBOB, LiSbF6, LiAsF6, LiCF3SO3, LiDFOB, LiDFOP, LiN(SO2CF3)2, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiClO4, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, lithium lower aliphatic carboxylate having 4 or less carbon atoms, and lithium tetraphenylborate.
[0057] Specifically, in some embodiments of the present invention, the mass percentage of the graphite is 85% to 100%, based on the total mass of the negative electrode active material being 100%. The graphite includes, but is not limited to, one or more of natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. Controlling the content of the graphite within the above range can allow the additive A to more fully form a negative electrode film and protect the negative electrode.
[0058] The negative electrode active material also includes a silicon-based material. Specifically, the silicon-based material is selected from one or more of silicon materials, silicon oxide materials, silicon-carbon materials and silicon alloy materials; preferably, the silicon material is a nano-silicon material; preferably, the silicon oxide material is SiO x Preferably, the silicon-carbon material is a silicon-based material containing silicon and carbon materials and / or a silicon-based material containing SiO y and a silicon-based material of a carbon material, wherein 0≤y<2; preferably, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material.
[0059] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductor.
[0060] Specifically, in some embodiments of the invention, the negative electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.
[0061] The negative electrode conductive agent includes one or more of conductive carbon black, conductive carbon spheres, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene, or reduced graphene oxide.
[0062] Specifically, in some embodiments of the present invention, the negative electrode current collector includes a metal material capable of conducting electrons. Preferably, the negative electrode current collector includes one or more of aluminum, nickel, tin, copper, and stainless steel.
[0063] Specifically, in some embodiments of the present invention, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes LiNi x Co y Mn z L (1-x-y-z) O2, LiCo x’ L (1-x’) O2, LiNi x” L’ y’ Mn (2-x”-y’) O4, Li z’ MPO4; wherein, L is one or more of Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, or Fe, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < x + y + z ≤ 1, 0 < x’ ≤ 1, 0.3 ≤ x” ≤ 0.6, 0.01 ≤ y’ ≤ 0.2, L’ is one or more of Co, Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, Fe; 0.5 ≤ z’ ≤ 1, M is one or more of Fe, Mn, Co. Preferably, the positive electrode active material includes LiCoO2, LiFePO4, LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.5 Co 0.2 Mn 0.2 Al0.1 O2、LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.
[0064] Specifically, in some embodiments of the present invention, the positive electrode further comprises a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector. The material of the positive electrode current collector may be the same as that of the negative electrode current collector, which will not be described in detail herein.
[0065] Specifically, in some embodiments of the present invention, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer. The positive electrode binder and the positive electrode conductor may be the same as the negative electrode binder and the negative electrode conductor, respectively, and will not be described in detail here.
[0066] Specifically, in some embodiments of the present invention, the lithium-ion battery further includes a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode.
[0067] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.
[0068] In the lithium ion battery of the present invention, the non-aqueous electrolyte includes a first additive as a negative electrode protection additive and a second additive as a positive electrode protection additive, and the relationship between the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive in the non-aqueous electrolyte, the order degree R of the negative electrode active material and the ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery is limited to satisfy 2≤[(A+B) / R]×Y≤48, 0.1≤A≤3, 0.5≤B≤5, 0.1≤R≤1, 0.8≤Y≤1.8, which can greatly reduce the degradation of the negative electrode by nitriles, form a stable interface film on the positive and negative electrode surfaces, and optimize the high temperature cycle performance of the lithium ion battery. DETAILED DESCRIPTION
[0069] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0070] Example 1
[0071] The method for preparing a lithium-ion battery in this embodiment comprises the following steps:
[0072] 1) Preparation of electrolyte
[0073] Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), propyl propionate (PP) and ethyl propionate (EP) are mixed in a mass ratio of EC:PC:DEC:PP:EP=10:15:20:40:15, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and then 4% 1,3-propane sultone and 5% fluoroethylene carbonate are added based on the total mass of the electrolyte, and then a first additive (compound 1) and a second additive are added. The content of the first additive and the type and content of the second additive are shown in Table 1.
[0074] 2) Preparation of positive electrode
[0075] The positive electrode active material lithium nickel cobalt manganese oxide LiNi was mixed in a mass ratio of 93:4:3 0.5 Co 0.2 Mn 0.3 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain a positive electrode sheet with a thickness of 120-150μm.
[0076] 3) Preparation of negative electrode
[0077] The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and the nickel lead wire is welded with an ultrasonic welder to obtain the negative electrode sheet, the thickness of which is 120-150μm.
[0078] 4) Preparation of battery cells
[0079] A three-layer separator with a thickness of 20 μm is placed between the positive electrode sheet and the negative electrode sheet, and then the sandwich structure consisting of the positive electrode sheet, the negative electrode sheet and the separator is wound. The wound body is flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.
[0080] 5) Battery filling and formation
[0081] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 24 hours. Then, the first charge was performed by hot pressing at 80 degrees according to the following steps: 0.1C constant current charging for 4 minutes, pressure 12.51kg / cc; 0.3C constant current charging for 15 minutes, pressure 12.51kg / cc; 1C constant current charging for 45 minutes, pressure 12.51kg / cc; secondary vacuum sealing, and then further charging at a constant current of 0.2C to the upper limit voltage, after being left at room temperature for 24 hours, discharged at a constant current of 0.2C to 3.0V.
[0082] Examples 2-42 and Comparative Examples 1-14
[0083] This embodiment and comparative example are used to compare and illustrate the lithium-ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the differences are: the composition and content of the additive in the non-aqueous electrolyte, the order of the negative electrode active material, and the ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery, as shown in Tables 1-6.
[0084] Table 1
[0085]
[0086]
[0087] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests as follows:
[0088] 1. High temperature cycle performance test
[0089] The prepared lithium-ion battery was placed in an oven at a constant temperature of 45°C, charged at a constant current of 1C to the upper limit voltage of the battery, then charged at a constant voltage until the current drops to 0.02C, and then discharged at a constant current of 1C to 3.0V. This cycle was repeated, and the first discharge capacity and the 500th discharge capacity were recorded.
[0090] The capacity retention rate of high temperature cycle is calculated as follows:
[0091] Capacity retention rate (%) = 500th discharge capacity / 1st discharge capacity × 100%.
[0092] 2. High temperature storage performance test
[0093] High temperature storage performance test
[0094] The formed lithium-ion battery is charged to the upper limit voltage at room temperature with 1C constant current and constant voltage, and the initial discharge capacity and initial battery thickness of the battery are measured. Then, after being stored in a 60°C environment for 30 days, it is discharged to 3V at 1C, and the battery retention capacity and recovery capacity as well as the battery thickness after storage are measured. The calculation formula is as follows:
[0095] Battery capacity retention rate (%) = retention capacity / initial capacity × 100%;
[0096] Battery capacity recovery rate (%) = recovery capacity / initial capacity × 100%;
[0097] Thickness expansion ratio (%) = (battery thickness after storage - initial battery thickness) / initial battery thickness × 100%.
[0098] (1) The test results of Examples 1-21 and Comparative Examples 1-14 are shown in Table 2.
[0099] Table 2
[0100]
[0101]
[0102]
[0103] It can be seen from the test results of Examples 1-21 and Comparative Examples 1-14 that in the lithium ion battery of the present invention, the additive in the non-aqueous electrolyte adopts the second additive as the positive electrode protection additive, and adopts the first additive as the negative electrode protection additive, and the relationship between the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive in the non-aqueous electrolyte, the degree of order R of the negative electrode active material and the ratio Y of the mass of the non-aqueous electrolyte of the lithium ion battery to the discharge capacity satisfies 2≤[(A+B) / R]×Y≤48, 0.1≤A≤3, 0.5≤B≤5, 0.1≤R≤1, and 0.8≤Y≤1.8, which can greatly reduce the degradation of the negative electrode by nitriles, form a stable interface film on the surface of the positive and negative electrodes, reduce the influence of excessive consumption of electrolyte on the battery performance, and further optimize the high temperature cycle performance of the lithium ion battery.
[0104] It can be seen from the test results of Example 1 and Comparative Examples 1-14 that when any one or more of the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive in the non-aqueous electrolyte, the order R of the negative electrode active material, and the ratio Y of the mass of the non-aqueous electrolyte of the lithium ion battery to the discharge capacity do not meet the specified range, or the value of the relationship [(A+B) / R]×Y is too large or too small, the lithium ion battery cannot be guaranteed to have good cycle performance; this indicates that the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive in the non-aqueous electrolyte, the order R of the negative electrode active material, and the ratio Y of the mass of the non-aqueous electrolyte of the lithium ion battery to the discharge capacity have a strong correlation in improving the high temperature cycle performance of the lithium ion battery.
[0105] (3) The test results of Example 1 and Examples 22-32 are shown in Table 3.
[0106] Table 3
[0107]
[0108]
[0109] It can be seen from the test results of Example 1 and Example 22-32 in Table 3 that for the non-aqueous electrolyte of the present invention, when the total content of the second additive in the additive is certain, three different combinations of nitriles of succinonitrile, adiponitrile and 1,3,6-hexane trinitrile are used as positive electrode protection additives, as long as the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive, the order degree R of the negative electrode active material, and the ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery meet the corresponding conditions, they can all play a role in protecting the positive electrode and optimize the high temperature cycle performance of the battery, indicating that the battery system of the present invention has universality for the above three second additives as positive electrode protection additives. In particular, when three nitrile compounds are contained at the same time, the high temperature storage performance and high temperature cycle performance of the battery are better than those containing one or two nitrile compounds, indicating that the positive electrode can be better protected by combining dinitriles and trinitriles of different molecular chain lengths and steric hindrances, further improving the high temperature storage performance of the battery without deteriorating the high temperature cycle performance.
[0110] (4) The test results of Example 1 and Examples 33-36 are shown in Table 4. The difference between Examples 33-36 and Example 1 lies in the relevant parameters in Table 4.
[0111] Table 4
[0112]
[0113] It can be seen from the test structures of Example 1 and Examples 33-36 in Table 4 that for the non-aqueous electrolyte of the present invention, when different first additives are used in the additives, when the mass percentage A of the first additive, the mass percentage B of the second additive, the order R of the negative electrode active material, and the ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery in the non-aqueous electrolyte all meet the corresponding conditions, the purpose of optimizing the high temperature cycle performance of the lithium-ion battery can be achieved; this shows that the battery system of the present invention is universal for different first additives, and can play a role in protecting the negative electrode of the battery within a limited protection range.
[0114] (4) The test results of Example 1 and Examples 37-38 are shown in Table 5. The difference between Examples 37-38 and Example 1 lies in the relevant parameters in Table 5.
[0115] Table 5
[0116]
[0117] From the comparison of the test results of Example 1 and Examples 37-38 in Table 5, it can be seen that in the lithium ion battery of the present invention, the additional addition of additives such as vinyl sulfate (DTD) and vinylene carbonate (VC) to the non-aqueous electrolyte can further optimize the high temperature cycle performance of the lithium ion battery, indicating that there is a complementary effect between the additives of the present invention and the auxiliary additives.
[0118] (5) The test results of Example 1 and Examples 39-42 are shown in Table 6. The difference between Examples 39-42 and Example 1 lies in the relevant parameters in Table 6.
[0119] Table 6
[0120]
[0121] It can be seen from the test results of Example 1 and Examples 39-42 in Table 6 that for the lithium ion battery of the present invention, when different negative electrode active materials are used, when the mass percentage A of the first additive in the non-aqueous electrolyte, the mass percentage B of the second additive in the non-aqueous electrolyte, the order R of the negative electrode active material and the ratio Y of the mass of the lithium ion battery non-aqueous electrolyte to the discharge capacity meet the corresponding conditions, the high temperature cycle performance of the lithium ion battery can be optimized, indicating that the battery system of the present invention is universal for different negative electrode active materials.
[0122] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A lithium ion battery, characterized in that: Including positive electrode sheet, negative electrode sheet and non-aqueous electrolyte; The negative electrode sheet comprises a negative electrode material layer containing a negative electrode active material, wherein the negative electrode active material comprises graphite, and the order degree of the negative electrode active material is R=I D / I G In the spectrum measured by Raman spectroscopy of the negative electrode using a laser with a wavelength of 532nm to 785nm, I D Appears at 1300cm -1 Up to 1400cm -1 The peak intensity of the inner D peak, I G Appears at 1530cm -1 Up to 1630cm -1 Peak intensity of inner D peak; The non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive; The additives include a first additive and a second additive, wherein the first additive includes at least one of the following compounds: The second additive includes at least one of succinonitrile, adiponitrile or 1,3,6-hexanetrinitrile; The lithium-ion battery meets the following requirements: 2≤[(A+B) / R]×Y≤48, 0.1≤A≤3, 0.5≤B≤5, 0.1≤R≤1, 0.8≤Y≤1.8; Wherein, A is the mass percentage of the first additive in the non-aqueous electrolyte, in %; B is the mass percentage of the second additive in the non-aqueous electrolyte, in %; R is the degree of order of the negative electrode active material; Y is the ratio of the mass of the non-aqueous electrolyte to the discharge capacity of the battery, in g / Ah.
2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery satisfies the condition: 2.8≤[(A+B) / R]×Y≤28.
3. The lithium-ion battery according to claim 1, characterized in that The mass percentage A% of the first additive in the non-aqueous electrolyte is 0.5% to 2%.
4. The lithium-ion battery according to claim 1, characterized in that: The mass percentage B% of the second additive in the non-aqueous electrolyte is 2% to 4%.
5. The lithium-ion battery according to claim 1, characterized in that: The order degree R of the negative electrode active material is 0.3 to 0.
8.
6. The lithium-ion battery according to claim 1, characterized in that The ratio Y of the mass of the non-aqueous electrolyte to the discharge capacity of the battery is 0.9 g / Ah to 1.4 g / Ah.
7. The lithium-ion battery according to claim 1, characterized in that: The second additive includes 1,3,6-hexanetrinitrile and succinonitrile; or, the second additive includes 1,3,6-hexanetrinitrile and adiponitrile.
8. The lithium-ion battery according to claim 1, characterized in that The non-aqueous electrolyte further includes an auxiliary additive, wherein the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, and a borate compound; and / or, Taking the mass of the non-aqueous electrolyte as 100%, the mass percentage of the auxiliary additive is 0.01% to 10%.
9. The lithium-ion battery according to claim 8, characterized in that: The cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of the compounds shown in the following structural formula 2: In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or, The borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
10. The lithium ion battery according to claim 1, characterized in that: Taking the total mass of the negative electrode active material as 100%, the mass percentage of the graphite is 85% to 100%.
Citation Information
Patent Citations
Lithium ion battery
CN115064770A
Lithium ion battery
CN116404253A
Lithium ion battery
CN118867376A
Nonaqueous electrolytic solution and energy storage device using the same
US20170373348A1
Lithium-ion battery
WO2024104100A1